Analisis Sistem Informasi Akuntansi Penjualan terhadap Proses Penagihan Piutang - Saverina, Rufina; Nurjanah, Yayuk (Jurnal Ilmiah Akuntansi Kesatuan, 2017)
The development of knowledge and the technology is rapidly changing causing tight competition in the business. To survive this competition and maintain sustainability, companies conduct various kinds of ways, one of which is by way of monitoring the system that existed in the corporate setting. One of the systems must be considered is a system of corporate sales and also the process of billing receivable. This is because sales are the activities that will produce revenues or profits for the company to maintain sustainability of its business. In this receivable billing activities, one must also considere whether or not the profit or assets owned by the company will give returns. The purpose of this research is to find out accounting information system sales, to know the process of billing receivable, and to know accounting system information of sales on the process billing receivable. The research was conducted in PT. Semut Merah Tangguh – branch Ciawi, Bogor. PT. Semut Merah Tangguh is the distributor company of consumer goods from PT.Unilever. The main activities of PT. Semut Merah Tangguh is placing order for a product from its principal company, namely PT .Unilever. Once the products have arrived, PT. Semut Merah Tangguh will offer promotional bids, sales, and billing to customers. The research results show that PT Semut Merah Tangguh has been running a proper process of debt of receivable, and adequately run its internal control fairly well. Nevertheless, there are still shortcomings in the company activities, such as the existence of doubled function in the sales department, the function of authorizing credit, and function of billing. It is recommended that PT. Semut Merah Tangguh - branch ciawi, Bogor must made immediate changes in several matters, such as the lack of serial number in the printed documents. The company already perform billing customers under average collections period become cash.